Ser/Thr phosphorylation of Mycobacterium tuberculosis type II RelK toxin by PknK destabilizes TA interaction and interferes with toxin neutralization - Shafinaz Rahman Sarah; Abhishek Garg; Sadiyah Afroz; Shaleen Korch; Arjun Ray; Amita Gupta; Vandana Malhotra (mBio, 2025)
ABSTRACT Toxin-antitoxin (TA) modules represent genetic elements implicated in bacterial persistence. Mycobacterium tuberculosis encodes 90+ TA modules, the majority of which are type II, comprising of a toxin component and an antitoxin counterpart that neutralizes the toxin. Under stressful environments, the antitoxin is degraded, releasing the toxin which then acts to halt cellular growth. Towards elucidating the underlying regulatory mechanisms that govern a synchronized TA cellular program, we explored the regulation of type II TA modules by post-translational modification. In silico analysis revealed that ~85% of M. tuberculosis TA proteins possess potential Ser/Thr phosphorylation sites, implicating them as targets for mycobacterial Ser/Thr protein kinases (STPKs). We demonstrate that members of the RelBE family interact with PknK, a stress-responsive STPK using the mycobacterial protein fragment complementation (M-PFC) assay and are subjected to Ser/Thr phosphorylation in vitro. LC-MS/MS confirmed multiple sites of phosphorylation in the RelJK module. Results from molecular dynamics simulations, in vitro binding, and co-expression studies with RelJK proteins indicate that the secondary structure changes associated with Thr77 phosphorylation in RelK toxin compromise its binding to the RelJ antitoxin. Substitution of Thr77 with alanine or glutamate in RelK toxin resulted in poor binding to the RelJ antitoxin, allowing a partial rescue of cells co-expressing wild-type RelJ antitoxin and RelK phosphorylation-deficient (T77A) or phosphomimetic (T77E) mutant toxins vs wild-type RelJK proteins. These findings implicate the RelK Thr77 residue at the toxin-antitoxin interaction interface and, more importantly, establish toxin phosphorylation as a novel mechanism influencing interaction dynamics of the TA module components.IMPORTANCEBacterial pathogens rely on the phenomenon of persistence as a survival strategy to combat the adverse environmental conditions encountered during infection. As a stochastic process, the driving force(s) that potentiate the formation of persisters in a bacterial population are largely unclear. This study is a step towards the discovery of intricate regulatory mechanisms that coordinate a synchronized TA cellular program. We propose a model where the TA module is regulated post-translationally, specifically via Ser/Thr phosphorylation disrupting the interaction between the toxin and antitoxin proteins as a mechanism to regulate TA function.